2023
DOI: 10.3389/fpsyg.2023.1160020
|View full text |Cite
|
Sign up to set email alerts
|

Social support score in patients with malignant diseases—with sociodemographic and medical characteristics

Snezana Corovic,
Veroljub Vucic,
Olgica Mihaljevic
et al.

Abstract: IntroductionSocial support as a complex construct has a positive influence not only on a patient’s condition but also on the process of the patient’s emotional adjustment to cancer. The goal of this study is to investigate aspects of the level of social support in oncology patients and its interconnection with sociodemographic and medical variables.MethodThe study was conducted as a prospective observational study in 2020, including 250 patients aged 19 and over, both sexes, with a diagnosis of oncological dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…The importance of social support in improving positive treatment outcomes for people with chronic diseases and conditions has been confirmed in previous research [11,16,19,23]. Studies have shown that cancer patients who have higher levels of social support have a better quality of life and lower mortality rates [30,31]. Social support has been identified as one of the key factors in the daily lives of cancer patients [32].…”
Section: Discussionmentioning
confidence: 73%
“…The importance of social support in improving positive treatment outcomes for people with chronic diseases and conditions has been confirmed in previous research [11,16,19,23]. Studies have shown that cancer patients who have higher levels of social support have a better quality of life and lower mortality rates [30,31]. Social support has been identified as one of the key factors in the daily lives of cancer patients [32].…”
Section: Discussionmentioning
confidence: 73%